2013
DOI: 10.3324/haematol.2013.090233
|View full text |Cite
|
Sign up to set email alerts
|

Immature MEF2C-dysregulated T-cell leukemia patients have an early T-cell precursor acute lymphoblastic leukemia gene signature and typically have non-rearranged T-cell receptors

Abstract: ABD cases) possibly representing early maturation arrest before the onset of T-cell receptor rearrangements.12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 43 publications
(106 reference statements)
7
80
0
1
Order By: Relevance
“…The poor prognosis of ETP phenotype, however, is increasingly contested in adult 21 and even pediatric T-ALL. 22 We performed SET-NUP214 RT-PCR screening in 22 AML overexpressing HOXA genes, including 5 minimally differentiated AML (French-American-British AML-M0) patients. One AML-M0 patient was SET-NUP214-positive.…”
Section: Cd2mentioning
confidence: 99%
“…The poor prognosis of ETP phenotype, however, is increasingly contested in adult 21 and even pediatric T-ALL. 22 We performed SET-NUP214 RT-PCR screening in 22 AML overexpressing HOXA genes, including 5 minimally differentiated AML (French-American-British AML-M0) patients. One AML-M0 patient was SET-NUP214-positive.…”
Section: Cd2mentioning
confidence: 99%
“…[3][4][5][6] Notably, the recently described early T-cell precursor (ETP)-acute lymphoblastic leukemia (ALL) patients 7 have leukemic cells that show an early block in T-cell differentiation and significantly overlap with LYL1-positive T-ALL 4 and MEF2C-dysregulated immature T-ALL. 5,8 These immature T-cell leukemias often express myeloid markers such as CD13 and CD33, and show a transcriptional program related to hematopoietic stem cells and myeloid progenitors. 5 Importantly, these tumors are associated with poor prognosis and reduced overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, the initial study that defined ETP-ALL as a novel immature subtype of pediatric human T-ALL, reported an extremely poor clinical course for these patients with 10-year overall survival rates of 19% for ETP-ALL patients as compared to 84% for other T-ALL subtypes [43]. Although the poor clinical characteristics of this leukemic subtype were subsequently validated in a variety of independent patient series from different international pediatric T-ALL treatment protocols [24,[43][44][45][46], more recent work has started to question the prognostic relevance of this aggressive T-ALL subtype [23,47]. In that context, a very recent and large study on 1144 pediatric T-ALL patients enrolled in the Children's Oncology Group (COG) Study AALL0434 suggested that, despite significantly higher rates of induction failure, pediatric ETP-ALL patients, as defined by flow cytometry in a single reference laboratory, show identical 5-year event-free and overall survival rates as compared to non-ETP-ALLs [48].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
“…These studies showed that the genetic landscape of immature T-ALL is highly heterogeneous with aberrant expression of the MEF2C gene [23,24], genetic alterations in hematopoietic transcription factors such as RUNX1, GATA3, BCL11B, PU.1 and ETV6 [24], activating mutations in critical mediators of cytokine receptor and RAS signaling, including NRAS, KRAS, FLT3, IL7R, JAK1, JAK3, SH2B3 and BRAF; as well as mutations in the epigenetic regulators EZH2, EED, SUZ12, MLL2, BMI1, SETD2 and EP300; as well as mutations in the dynamin coding gene DNM2 [8,25]. In addition, immature T-ALLs present with lower frequencies of the prototypical NOTCH1 mutations, which occur in the majority of mature T-ALL patient samples and are considered one of the hallmarks of human T-cell transformation.…”
Section: Accepted Manuscriptmentioning
confidence: 97%